Inibição de Listeria monocytogenes em salsicha por Leuconostoc mesenteroides isolada de grãos de Kefir - Murielle Ferreira de Morais (2015)
Some strains of lactic acid bacteria (LAB) have the ability to produce antimicrobial substances that control/inhibit spoilage microorganisms and/or pathogens, such as Listeria monocytogenes. In this study, 12 LAB strains isolated from kefir, belonging to the genera Lactobacillus, Lactococcus and Leuconostoc were evaluated in a 1st stage (stage 1) through inhibitory activity tests by Spot-on-the-lawn method and well diffusion assay, resulting in pre-selection of four LAB. These LAB were evaluated for inhibitory potential against four strains of L. monocytogenes from different serotypes (1/2a, 4a, 4b and an isolated sausage strain). The LAB strain Leuconostoc mesenteroides showed the highest inhibition halo, and L. monocytogenes serotype with the highest sensitivity was 4b. In a 2nd stage (stage 2), samples of sausages, sterilized by irradiation, were inoculated with L. mesenteroides and L. monocytogenes 4b strains (alone or in combination), and also commercial nisin (Nisaplin®) resulting in BL (L. monocytogenes), BLN (L. monocytogenes and Nisin), BLB (L. monocytogenes and L. mesenteroides) and BB (L. mesenteroides) treatments, which were used to evaluate BAL strain and commercial nisin (Nisaplin®) inhibitory activity against L. monocytogenes. The samples were stored under refrigeration at 10° C and analyzed in five times (first, 1st, 2nd, 4th and 8th week). These samples, at first, showed means of L. monocytogenes counts of 2.77 log CFU g-1 in BL, 1.55 log CFU g-1 in BLN, 2.66 log CFU.g-1 in BLB, and L. mesenteroides count of 6.1 log CFU g-1 in BB. During storage period, L. monocytogenes counts increased. However, BLB treatment revealed a smaller increase in counts (p <0.05) with an observed variation of 5.90 log CFU g -1; 7.14 log CFU g-1 and 2.73 log CFU g-1 to BL, BLN and BLB, respectively. From the 2nd week to the end of the storage period, the inhibitory activity of L. mesenteroides strain was higher than that of commercial nisin. These results suggest that L. mesenteroides, selected from kefir, have promising potential in bio preservation, by inhibitory substances (similar to bacteriocins) production capacity with antagonistic effect against strains of L. monocytogenes, superior even to commercial nisin, in some ready-to-eat sausage-like products.